A randomized, double-blind, placebo-controlled clinical study to evaluate the efficacy and safety of Weizmannia coagulans BC99 in the treatment of chronic constipation in adults - Wu, Ying; Bai, Zhouya; Jin, Yuehong; Zhu, Hong; Dong, Yao; Gu, Shaobin; Jin, Ying (Frontiers in Nutrition, 2024)
Weizmannia coagulans has emerged as a promising candidate for the management of gastrointestinal ailments. The novel strain of Weizmannia coagulans, Weizmannia coagulans BC99 (BC99), displays robust pathogen-inhibiting capabilities, susceptibility to various antibiotics, and a high level of biosafety. Nevertheless, additional research is necessary to fully understand its effectiveness in managing chronic constipation. Thus, this study investigates the role of BC99 in alleviating chronic constipation in a double-blind, placebo-controlled, randomized trial, and participants were divided into BC99 (2 billion CFU/d) or placebo (maltodextrin) groups for a four-week period. Results showed that significant improvements were noted in the BC99 group, with an increase in complete spontaneous bowel movements (CSBM) after 4-week treatment compared to the placebo (p = 0.002). The BC99 group also showed significantly lower Quality of Life (PAC-QOL) scores and reduced Constipation Symptoms (PAC-SYM) scores after four weeks of treatment (p < 0.001), indicating symptomatic relief. Notably, BC99 effectively modulated key gut microbiota such as Bifidobacterium and Ruminococcus, linked to crucial metabolic pathways like glutathione metabolism. In all, BC99 is confirmed to be an effective and safe therapeutic option for the relief of adult chronic constipation, enhancing gut microbiota balance and influencing critical metabolic pathways.